Time and Narrative: An Investigation of Storytelling Abilities in Children With Autism Spectrum Disorder - Ferretti, Francesco; Adornetti, Ines; Chiera, Alessandra; Nicchiarelli, Serena; Valeri, Giovanni; Magni, Rita; Vicari, Stefano; Marini, Andrea (Frontiers in Psychology, 2018)
This study analyzed the relation between mental time travel (MTT) and the ability to produce a storytelling focusing on global coherence, which is one of the most notable characteristics of narrative discourse. As global coherence is strictly tied to the temporal sequence of the events narrated in a story, we hypothesized that the construction of coherent narratives would rely on the ability to mentally navigate in time. To test such a hypothesis, we investigated the relation between one component of MTT—namely, episodic future thinking (EFT)—and narrative production skills by comparing the narratives produced by 66 children with high-functioning autism spectrum disorder (ASD) with those uttered by 66 children with typical development. EFT was assessed by administering a task with minimal narrative demands, whereas storytelling production skills were assessed by administering two narrative production tasks that required children to generate future or past episodes with respect to the target stimuli. The results showed that EFT skills were impaired only in a subgroup of children with ASD and that such subgroup performed significantly worse on the narrative generation task than ASD participants with high EFT skills and participants with typical development. The practical and theoretical implications of these findings are discussed.